2007
DOI: 10.1016/j.brainres.2007.01.099
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NGF and NT-3 protein expression in peripheral targets by sympathetic input

Abstract: Nerve growth factor (NGF) and neurotrophin-3 (NT-3) are target-derived proteins that regulate innervating sympathetic neurons. Here, we used western blot analysis to investigate changes in NGF and NT-3 protein in several peripheral tissues following loss of sympathetic input. Following removal of the superior cervical ganglion (SCG), large molecular weight (MW) NGF species, including proNGF-A, were increased in distal intracranial SCG targets, such as pineal gland and extracerebral blood vessels (bv). Mature N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 48 publications
2
23
0
1
Order By: Relevance
“…Western blotting analysis revealed the presence of pro and mature forms of NGF and BDNF in all tracts, similarly to results reported in the uterus of mammals (Li et al, 2012;Wessels et al, 2014), and only one band corresponding to proNT-3, as described in pineal glands, extracerebral blood vessels and external carotid (Randolph et al, 2007). With regard to Trks, in the oviduct TrkA showed a molecular weight of 80 kDa, consistent with the molecular weight of non-glycosylated full length receptor.…”
Section: Discussionsupporting
confidence: 84%
“…Western blotting analysis revealed the presence of pro and mature forms of NGF and BDNF in all tracts, similarly to results reported in the uterus of mammals (Li et al, 2012;Wessels et al, 2014), and only one band corresponding to proNT-3, as described in pineal glands, extracerebral blood vessels and external carotid (Randolph et al, 2007). With regard to Trks, in the oviduct TrkA showed a molecular weight of 80 kDa, consistent with the molecular weight of non-glycosylated full length receptor.…”
Section: Discussionsupporting
confidence: 84%
“…Further, pro-NGF protein increases only slightly after WBV, while, the high molecular weight 75kDa NGF species exhibits a robust (10-fold) (Figure 3). Although this higher molecular weight species has not been previously reported in the disc, it is prevalent in extracerebral blood vessels and the external carotid artery [39]. Freemont et al (2002) reported microvascular blood vessels expressing NGF adjacent to ingrown nerves in painful human lumbar IVDs [9].…”
Section: Discussionmentioning
confidence: 99%
“…of NGF, corresponding to 13.5 KDa, is a minor species whereas higher molecular weight species (22)(23)(24)34,55,and 75 KDa) are predominant (Randolph et al, 2007), we have further analyzed the expression of different forms of NGF in hippocampal cells. Our experiments showed in untreated samples different abundance of 75 KDa, 34 KDa, and 13 KDa NGF species in NFL and purified nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of the mature form could explain the differentiating effects of vitamin D3. Little is known on the function of the 75 KDa species, although an increase after denervation has been found (Randolph et al, 2007). One of the roles of the increased NGF could be the increase in the expression of neurofilaments, proteins that play a key role in the maintenance and remodeling of the neuronal cytoskeleton (Vaucher et al, 2001).…”
Section: Discussionmentioning
confidence: 99%